Pressure-Energy Optimization in Water Distribution Network (Case Study of Baharestan City in Isfahan) - Hossein Nasrollahi; Reza Safaei Boroujeni; Seyed Mohammad Hossein Saleh (علوم و مهندسی آب و فاضلاب, 2022)
Pressure management can reduce leakage and water loss in water distribution networks. Therefore, pressure management is considered as one of the most important ways to reduce costs related to the operation and maintenance of water distribution networks, especially in worn-out networks. Therefore, the pressure of water supplied to consumers should be as low as possible. This approach to reducing pressure in the distribution network by water and wastewater companies has led to an increase in the need for domestic water pressure boosting systems (using pumps and tanks), which in turn increases energy consumption. This discrepancy in the interests of water and wastewater companies and energy consumers highlights the perspective of the water-energy relationship. The aim of this study is to find a solution to optimize the pressure in water distribution networks through the use of domestic water pressure boosting systems while simultaneously minimize the total cost of leakage, pipe burst repairs and energy consumption. In this research, EPANET software is used for hydraulic analysis of the network as well as the use of pressure-based analysis to model as close as possible to the actual operating conditions. The research method has been implemented as a pilot for Baharestan city in Isfahan, and the results show that the optimal pressure is about 48 meters of water column and at a pressure of 41 meters, the costs of water and energy are equal.